A Reflective Study on Practical Methods for Developing Arabic Animation Learning Media Using Plotagon Story - Idrus, S. Ali Jadid al; Syarifuddin, M.; Cahyani, Leny; Raharja, Radin Paras (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
The teaching of Arabic across diverse institutions continues to encounter challenges related to student engagement, communicative context, and teachers’ capacity to present compelling instructional media. Animated media hold significant potential to enrich learning through the integration of visual, auditory, and narrative elements; however, their production is often perceived as complex and requiring advanced technical skills. This study aims to identify practical methods for producing Arabic-language animated learning media using Plotagon Story, employing a reflective qualitative approach within the Action Research framework developed by Kemmis and McTaggart. Training and mentoring were conducted in three partner pesantren through iterative cycles of planning, acting, observing, and reflecting. Data were collected via reflective interviews, observation of instructional practices, and documentation of the produced animations, and subsequently analysed using Thematic Analysis. The findings indicate that micro-staging, person-to-person mentoring, and hands-on practice constitute key factors in mitigating digital anxiety and enhancing teachers’ media literacy. Teachers initially unfamiliar with technology succeeded in producing instructional animations, including taʿāruf dialogues, school-related vocabulary, and classroom scenarios. Classroom observations revealed increased student attention, motivation, and comprehension when the teacher-produced animations were utilised. Participants’ reflections highlighted professional transformation, particularly in terms of increased self-efficacy and pedagogical awareness regarding the role of animation in providing authentic communicative contexts. The study concludes that Plotagon Story is a practical and accessible tool for developing Arabic-language instructional media, particularly in resource-limited settings. It contributes to the advancement of a simple, effective, and replicable model for training in digital media production.